Adoption of Recommended Technologies for Cassava Processing among Women in Ankpa, Kogi State, Nigeria - Ocheni, Benjamine; Eze, J. N.; Ugalahi, U. B; Dauda, N. S; Sallawu, H. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
Cassava is a vital crop in Nigeria, providing food, income, and employment opportunities for millions of people. However, processing of cassava require a lot of labor and is known for its poor productivity and value. This study investigated the acceptance of recommended modern technologies for cassava processing among women processors in Ankpa, Kogi State, Nigeria. A survey of 152 women cassava processors was conducted using structured questionnaires. The research outcome showed that the sampled respondents were predominantly between 21-40 years old, married, and had primary education. The acceptance rate of recommended technologies for cassava processing was fairly high, with mechanical grater having the highest adoption rate of 100%. The study identified age, household size, and processing experience as significant factors influencing the adoption of recommended cassava processing technologies. The results also showed that women processors with larger household sizes and more processing experience were more likely to adopt recommended technologies. The study concludes that empowering women cassava processors through provision of funds, credit schemes, and extension services can enhance their participation in cassava processing and improve their livelihoods. The study recommends the provision of modern machines and equipment to ease the drudgery associated with cassava processing and improve productivity and quality.